2017
DOI: 10.1037/npe0000074
|View full text |Cite
|
Sign up to set email alerts
|

Mental accounting in decision-making for self versus others.

Abstract: Previous studies have commonly used the third-person format to explore the generality of mental accounting and have observed the mental accounting effect when people predict others’ behavior. However, little is known about whether the mental accounting effect can be observed when people make decisions for others. We conducted 2 studies to investigate this issue. In Study 1, participants were asked to read all A or B scenarios for 3 modified mental accounting problems (the movie ticket problem, the sneaker and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
(94 reference statements)
0
7
0
1
Order By: Relevance
“…Studies (Z. Liu et al, 2017; C. Liu et al, 2018) show that consumers mentally differentiate between money and spending that is relevant to themselves or to others. In general, MA effects seem to be weaker when individuals make decisions for others, regardless of whether the other person is socially close or distant (Z. Liu et al, 2017). A study by C. Liu et al (2018) shows that the source of funds can also have an effect on how self‐relevant purchases are.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies (Z. Liu et al, 2017; C. Liu et al, 2018) show that consumers mentally differentiate between money and spending that is relevant to themselves or to others. In general, MA effects seem to be weaker when individuals make decisions for others, regardless of whether the other person is socially close or distant (Z. Liu et al, 2017). A study by C. Liu et al (2018) shows that the source of funds can also have an effect on how self‐relevant purchases are.…”
Section: Resultsmentioning
confidence: 99%
“…Studies (Z. Liu et al, 2017;C. Liu et al, 2018) show that consumers mentally differentiate between money and spending that is relevant to themselves or to others.…”
Section: Self-relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals make financial decisions for themselves and for others. A growing body of literature on self–other discrepancies has suggested that decision makers (i.e., people who make decisions) perform differently when they decide for others rather than for themselves (e.g., Y. Liu, Polman, Liu, & Jiao, 2018; Z. Liu, Liu, & Mu, 2017; Lu, Jia, Xie, & Wang, 2016; Lu & Xie, 2014; Lu, Xie, & Xu, 2012; Polman, 2012; Polman & Vohs, 2016; Tunney & Ziegler, 2015). A decision target (i.e., whether the decision is made for oneself or others) influences decision makers' behaviors (Lu et al, 2012), especially on risk‐related decisions (e.g., Andersson, Holm, Tyran, & Wengström, 2016; Polman & Wu, 2020; Stone & Allgaier, 2008; Sun, Liu, Zhang, & Lu, 2016).…”
Section: Self–other Decision Differencesmentioning
confidence: 99%
“…A growing body of literature on self-other discrepancies has suggested that decision makers (i.e., people who make decisions) perform differently when they decide for others rather than for themselves (e.g., Y. Liu, Polman, Liu, & Jiao, 2018;Z. Liu, Liu, & Mu, 2017;Lu, Jia, Xie, & Wang, 2016;Lu & Xie, 2014;Lu, Xie, & Xu, 2012;Polman, 2012;Polman & Vohs, 2016;Tunney & Ziegler, 2015).…”
Section: Self-other Decision Differencesmentioning
confidence: 99%